Strategi Meningkatkan Kesiapan Pasar Industri Indonesia di Era Puncak Revolusi Industri 4.0 - Bagus Hendra Stia Pratama; Mahardika Wahyu Pradana; Naerul Edwin Kiky Aprianto; Ridha Alfisya Rasyidin; Rifani Tri Handani (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This article presents a comprehensive analysis of the strategies needed to enhance the readiness of the industrial market in Indonesia, emphasizing government policies and their impact on industrial growth. In the context of globalization and the 4.0 industrial revolution, market readiness is crucial to ensure competitiveness and sustainability. The article examines various policies implemented by the government, such as investment incentives, infrastructure development, and support for research and development (R&D), to create an environment conducive to innovation and productivity. The development of human resources through vocational education and training is a primary focus, where skills relevant to industry needs are essential for producing competent and adaptive workers. By understanding the synergy between policies, innovation, and their impacts, this article aims to provide insights and guidance for stakeholders in formulating effective strategies to prepare Indonesian industries for challenges in the international market.